Mechanical Behaviors and Damage Constitutive Model of Thermally Treated Sandstone Under Impact Loading - Tubing Yin; Pin Wang; Jian Yang; Xibing Li (IEEE Access, 2018)
Thermal-mechanical coupling damage is an important factor leading to instability and failure of rock mass engineering. The constitutive relation and damage evolution of rock-like materials under high strain rate is crucial parameters for the design of underground rock mass structures, and is also an essential foundation for the analysis of instability phenomena in rock mass engineering. In this paper, a series of physical properties, static, and dynamic mechanical tests were carried out on Changsha sandstone after different high temperature treatments (ranging from 25 °C to 800 °C). Results indicate that thermal treatment effectively weakens the sandstone specimens. Under dynamic loading, the rock shows obvious strain rate effect, and the stress-strain curve changes from brittleness to viscoelasticity with the increase of temperature. Based on statistical damage theory and Weibull distribution, combining the analysis of the change laws of stress-strain curves of sandstone with temperature, a damage constitutive model that can reflect the variation in dynamic mechanical properties with temperature was proposed, for which the ultrasonic velocity is used to characterize the initial damage of rock caused by high temperature. Thereafter, the rationality of the constitutive model was verified by experiments. Combing damage evolution characteristics and rock failure process recorded by high-speed camera, the dynamic stress-strain relation curves of rock under different high temperature are divided into four stages, and the damage evolution process of rock under thermo-mechanical coupling was also analyzed. Results indicate that the values of thermo-mechanical damage increase exponentially with rock strain, and the damage evolution rate presents a two stage variation of first increase and then decrease. The initial damage stress of rock decreases with increasing temperature, but always maintains a stable percentage compared with the peak stress of the rock. Although the damage value at the peak point of stress increases with the increase of the temperature, it did not reach the maximum value of 1, which indicates that the rock damage continues to increase in the post peak loading stage. The findings of this paper can provide guidance for the macroscopic mechanical damage of rock under high temperatures and dynamic loading.